Case Report: Avoiding misdiagnosis in amyloidosis—navigating transthyretin genopositivity and monoclonal gammopathy in a patient with advanced heart failure and spinal stenosis - Xia Wu; Denis Toskic; Denis Toskic; Ping Zhou; Stephanie Scalia; Xun Ma; Parva Bhatt; Teresa Fogaren; Monika Pilichowska; Knarik Arkun; Knarik Arkun; Jainith Patel; et al. (Frontiers in Cardiovascular Medicine)
BackgroundA 63-year-old Black woman presented with progressive exertional dyspnea and chronic lower back pain. The course and findings in her case are instructive.Case reportFamily history was notable for cardiac deaths. An echocardiogram demonstrated ventricular wall thickening with diastolic dysfunction. The patient’s N-terminal pro b-type natriuretic peptide level was 1,691 pg/ml with a troponin I level of 0.36 ng/ml. Transthyretin (TTR) sequencing detected a heterozygous V122I variant. The patient’s free κ light chain level in serum was 664 mg/L with a ratio of 16.5. Bone marrow analysis showed 20%–30% κ-restricted plasma cells with amyloid deposits. A technetium-99m sodium pyrophosphate scan was performed and was negative. Magnetic resonance imaging of the total spine showed ligamentum flavum (LF) thickening at L4–5, causing severe spinal stenosis. In both the abdominal fat and the LF, liquid chromatography-coupled tandem mass spectrometry confirmed κ-type immunoglobulin light chain (AL) amyloidosis; the quantitative estimate of amyloid content in the LF was 5%. She was diagnosed with AL amyloidosis with Mayo Stage IIIA cardiac and soft tissue involvement, enrolled in the Aquarius trial (NCT05250973) in Cohort 2, and received daratumumab, cyclophosphamide, bortezomib, and dexamethasone. She achieved a partial hematological response with a cardiac response and is now pain-free and fully functional.ConclusionIn patients with amyloidosis who have both monoclonal gammopathy and a TTR variant, it is imperative to discern the tissue type of the amyloid to deduce the correct diagnosis. ATTR and AL amyloidosis can both cause spinal stenosis with minimal degenerative changes. The LF tissue must be stained for amyloids and, if present, typing must be performed.